2019
DOI: 10.1111/lam.13239
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of banana crop residue as an agricultural bioresource for the production of acetone‐butanol‐ethanol byClostridium beijerinckiiYVU1

Abstract: This study aimed to produce acetone‐butanol‐ethanol (ABE) using lignocellulosic crop residues as renewable bioresources. Butanol production from banana crop residue (BCR) was studied using a newly isolated solventogenic Clostridium beijerinckii YVU1. BCR is one of the abundant lignocellulosic substrates available in tropical countries containing 4·3 ± 3·5% cellulose, 28·5 ± 3·0% hemicellulose and 20·3 ± 2·6% lignin. The sequential dilute alkali and acid pretreatments solubilized 69% of lignin and 73% of hemice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To make a transition from these environmentally and human-threatening processes, scientists developed the acetone-butanol-ethanol fermentation route around the late 1800s and early 1900s [302,303], which traditionally used first-generation feedstocks like corn, cassava, sugarcane or wheat [304,305]. However, this process is still hindered by the low butanol yields and the high process costs [306,307]. Thus, recent studies are now using biomass residues (agricultural wastes, lignocellulosic wastes, and industrial wastes) alongside the cellulosic microbes found in various habitats to curb the process costs and pave the way for scale-up studies [308][309][310].…”
Section: Butanolmentioning
confidence: 99%
“…To make a transition from these environmentally and human-threatening processes, scientists developed the acetone-butanol-ethanol fermentation route around the late 1800s and early 1900s [302,303], which traditionally used first-generation feedstocks like corn, cassava, sugarcane or wheat [304,305]. However, this process is still hindered by the low butanol yields and the high process costs [306,307]. Thus, recent studies are now using biomass residues (agricultural wastes, lignocellulosic wastes, and industrial wastes) alongside the cellulosic microbes found in various habitats to curb the process costs and pave the way for scale-up studies [308][309][310].…”
Section: Butanolmentioning
confidence: 99%
“…Clostridium beijerinckii is a Gram-positive anaerobic solventogenic bacterium that is well known for its ability to produce acetone, butanol, and ethanol (ABE) or isopropanol, butanol, and ethanol (IBE) ( Qureshi and Blaschek 2001 ; Survase et al 2011 ; dos Santos Vieira et al 2020 ) using low-cost carbon sources, such as different straw hydrolysates ( Bellido et al 2014 ; Dalal et al 2019 ), lignocellulosic hydrolysate ( Reddy et al 2020 ), and molasses ( Li et al 2013 ; Fonseca et al 2020 ). In addition, it has been used to produce hydrogen with great success ( Seelert et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the world energy outlook 2015, fossil fuels such as coal, petrol products and natural gas are being used predominantly for energy requirements in various sectors, providing more than 80% of the world's energy between 2013 and 2035 [2]. Specifically, energy demands across the industrial and transport sectors are high compared to other sectors [3,4]. The gap between demand and supply of fossil fuels is increasing continuously, thereby raising prices in recent days, which, in turn, affects the economy of the country [5,6].…”
Section: Introductionmentioning
confidence: 99%